IMPLEMENTATION OF A SCHOOL INFORMATION SYSTEM USING RAPID APPLICATION DEVELOPMENT METHOD - Hariadi Suwandi; Harlinda Harlinda; Sitti Hajrah Mansyur (Informatika, Universitas Jenderal Soedirman, 2022)
The learning process in schools is the best public policy tool as an effort to increase knowledge and skills. In addition, many students think that school is a very fun activity, they can interact with each other. During the pandemic, the learning system has implemented a blended so that every school strives to have an information system. This study aims to assist the school and parents in processing student grades, school information related to academic and non-academic activities as well as communication space between teachers and parents. The method used is Rapid Application Development (RAD) which is intended to provide much faster development and successfully develops the system within 90 days with the stages of Requirements Planning, Workshop Design RAD and Implementation. Based on the questionnaire given in accordance with the 7 aspects of the web application testing criteria, content testing was obtained 55%, interface testing 32%, navigation testing 69%, component testing 32%, configuration testing 55%, performance testing 32% and security testing 51%. Based on the questionnaire given in accordance with black box testing, it was obtained by 88%. The results obtained were successful in creating a web and mobile-based Cambaya IV application that can be used as a processing of student grades, school information related to academic and non-academic activities as well as a communication room between teachers and parents in the form of a chat feature.